Pengaruh Ekstrak Rosela (Hibiscus Sabdariffa) terhadap Kadar Trigliserida Tikus Putih Diabetes - Adhy Nugroho, Christianto (Widya Warta, 2013)
Rosela is one of medicinal herbs. Rosela contents phytochemicals such as: gossypetine, hibiscin, flavonoid phenol, anthocyanin. The aim of the study was to find out the effect of oral intake of Rosela extract on triglyceride concentration of diabetic white rat. This research applied Experimental Method which concists of four groups with five replications to each. The treatment for each of those groups was: (1) normal rat without treatment, (2) diabetic rat without treatment of Rosela extract, (3) diabetic rat treated 250 mg/kg body weight of   Rosela extract, (4) diabetic rat   treated   500 mg/kg body weight of Rosela extract. The parameters used were triglyceride concentration. The result showed that the extract of Rosela reduced triglyceride concentration.